Unmanned Aerial Vehicle with Hybrid Lift and Propulsion - Lucena, Alysson Nascimento; Freire-Júnior, Raimundo Carlos Silvério; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Diminishing energy consumption with the greatest possible autonomy on flight time and distance is one of the main goals of the development of unmanned aerial vehicles (UAV). Vertical takeoff and landing is also another feature that makes it easier to handle such platforms. Considering these requirements, we introduce the architectural design of a UAV that is conceptualized and built as a flying wing with a pusher configuration with combustion engine propeller and a multirotor composed of 3 propeller sets with electric motors. We performed several tests, including takeoff, horizontal flight, and transition tests successfully, and also tests on autonomy. Results show the versatility of the final-built hybrid prototype for operations in the field. The hybrid system has proven to be functional and effective, such that the architectural sketch has been submitted as a patent. So the main contribution here is the architectural design and construction details of the hybrid UAV system composed of a multirotor with 3 electric powertrain sets and a flying wing with a combustion powertrain set.